Cyclooxygenase-2 mediates microglial activation and secondary dopaminergic cell death in the mouse MPTP model of Parkinson's disease - Vijitruth, Rattanavijit (BioMed Central, 2006)
BACKGROUND: Accumulating evidence suggests that inflammation plays an important role in the progression of Parkinson's disease (PD). Among many inflammatory factors found in the PD brain, cyclooxygenase (COX), specifically the inducible isoform, COX-2, is believed to be a critical enzyme in the inflammatory response. Induction of COX-2 is also found in an experimental model of PD produced by administration of 1-methy-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP). METHOD: COX-2-deficient mice or C57BL/6 mice were treated with MPTP to investigate the effects of COX-2 deficiency or by using various doses of valdecoxib, a specific COX-2 inhibitor, which induces inhibition of COX-2 on dopaminergic neuronal toxicity and locomotor activity impairment. Immunohistochemistry, stereological cell counts, immunoblotting, an automated spontaneous locomotor activity recorder and rotarod behavioral testing apparatus were used to assess microglial activation, cell loss, and behavioral impariments. RESULTS: MPTP reduced tyrosine hydroxylase (TH)-positive cell counts in the substantia nigra pars compacta (SNpc); total distance traveled, vertical activity, and coordination on a rotarod; and increased microglia activation. Valdecoxib alleviated the microglial activation, the loss of TH-positive cells and the decrease in open field and vertical activity. COX-2 deficiency attenuated MPTP-induced microglial activation, degeneration of TH-positive cells, and loss of coordination. CONCLUSION: These results indicate that reducing COX-2 activity can mitigate the secondary and progressive loss of dopaminergic neurons as well as the motor deficits induced by MPTP, possibly by suppression of microglial activation in the SNpc.